2015
DOI: 10.1161/circulationaha.114.013588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hemodynamic Outcomes up to 7 Years After Transcatheter Pulmonary Valve Replacement in the US Melody Valve Investigational Device Exemption Trial

Abstract: Background-Studies of transcatheter pulmonary valve (TPV) replacement with the Melody valve have demonstrated goodshort-term outcomes, but there are no published long-term follow-up data. Methods and Results-The US Investigational Device Exemption trial prospectively enrolled 171 pediatric and adult patients (median age, 19 years) with right ventricular outflow tract conduit obstruction or regurgitation. The 148 patients who received and were discharged with a TPV were followed up annually according to a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
227
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(248 citation statements)
references
References 30 publications
14
227
5
2
Order By: Relevance
“…Clinical trials have shown the safety and efficacy of TPVI, with excellent short‐term outcomes2 and freedom from reintervention in most patients up to 5 years 3. However, the risk of IE of the Melody valve is increasingly recognized as a significant threat to the long‐term valve function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical trials have shown the safety and efficacy of TPVI, with excellent short‐term outcomes2 and freedom from reintervention in most patients up to 5 years 3. However, the risk of IE of the Melody valve is increasingly recognized as a significant threat to the long‐term valve function.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial phase of TPVI experience, reobstruction of the RVOT with subsequent reintervention was relatively common, and it was mostly attributable to stent fracture 3. In the more contemporary TPVI experience, with the adoption of routine prestenting, reintervention attributable to recurrent valve obstruction became uncommon 4, 24, 61, 62.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcatheter pulmonary valve implantation (TPVI) with the Melody® transcatheter pulmonary valve (TPV) (Medtronic Inc, Minneapolis, United States) has demonstrated good haemodynamic and clinical outcomes in the treatment of RVOT conduit dysfunction in patients with repaired CHD (2,3). Numerous trial and registry data have demonstrated reduced RVOT gradients, elimination of pulmonary regurgitation or stenosis and good clinical outcomes early after implantation (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%